Demographic Profile, Respiratory Presentation and Outcome Analysis of Acute Encephalitis Syndrome in a Tertiary Hospital in Bangladesh - Binoy Krishna Tarafder; Mohammad Ashik Imran Khan; Dola, Taslima Ahmed; Shabnam, Mahbuba; Uddin, Md Mohi; Amin, Mohammad Ashraful; Saha, Radheshyam; Hawlader, Anisur Rahman; Miah, Md Titu (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Acute encephalitis syndrome has been a major health problem worldwide due to its high morbidity and mortality. The aim of this study was to find out the demographic profile of acute encephalitis syndrome and to determine the association of the outcome of the disease with the demographic factors and respiratory symptoms at presentation. This observational analytic cross-sectional study was conducted in the departments of Medicine, Paediatrics, and Neurology in Bangabandhu Sheikh Mujib Medical College Hospital in Bangladesh from September 2013 to August 2014. People of all ages who fulfilled the inclusion criteria of acute encephalitis syndrome were included in the study. In this study, 270 cases were diagnosed with acute encephalitis syndrome. Most cases were clustered around the age groups of 0-5 year (24.1%), 6-17 year (24.8%), and 18 -45 year (28.5%). Death was higher among the 18-45 age groups (33.3%) as well as in males (59.3%). Apart from neurological symptoms, respiratory symptoms on presentation were present in 66.9% cases with 89.6% death and this association was found statistically significant (p value < 0.001, AOR 6.96, COR 5.3 with 95% CI). Influence of socio-demographic factors and delay in seeking hospital admission on adverse outcome was not statistically significant. Most cases occurred in January-February (12.6% and 11.1%) and in July (14.4%). Overall mortality was 17.8%. Encephalitis presenting with respiratory symptoms in association carries higher mortality. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(1):22-26